First person - Claire L. Wood (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Claire Wood is first author on 'A comparison of the bone and growth phenotype of mdx, mdx:Cmah−/− and mdx:Utrn+/− murine models with the C57BL/10 wild-type mouse', published in DMM. Claire conducted the research described in this article while an MRC Clinical Research Training Fellow in Colin Farquharson's lab at Roslin Institute, University of Edinburgh, UK. She is now an academic clinical lecturer in the lab of Tim Cheetham and Simon Pearce at the Institute of Genetic Medicine, Newcastle University, UK, investigating bone and growth in children.